Coplanar Waveguide-Fed Bidirectional Same-Sense Circularly Polarized Metasurface-Based Antenna - Hilary, Cho; Nkimbeng, Scott; Wang, Heesu; Park, Ikmo (Journal of Electromagnetic Engineering and Science, 2021)
This paper presents the design of a bidirectional same-sense circularly polarized (CP) antenna that uses metasurfaces. The antenna consists of two metasurfaces, each comprising an array of 2 X 4 corner truncated patches placed back-to-back on the top and bottom of the antenna. In addition, a ground plane with an etched slot is sandwiched between the substrates at the front and back, and the feed line is a 50 Ω coplanar waveguide. The antenna radiates same-sense right-handed CP waves in both the front and back directions and has overall dimensions of 48 mm X 24 mm X 3.048 mm (0.91λo X 0.45λo X 0.05λo at 5.7 GHz). The measured reflection coefficient for |5u| < -10 dB yields an impedance bandwidth of 5.21-6.26 GHz (18.4%) and an axial ratio (AR) bandwidth of 5.36-6 GHz (11.2%) for both front and back directions. The antenna gain is 3-5.29 dBic for both directions and has a radiation efficiency of >96% within its AR bandwidth.
Keywords: Bidirectional Antenna; Circular Polarization; Metasurface; Same-Sense